Applications of the Bell Numbers on Univalent Functions Associated with Subordination. (10th March 2022) - Najafzadeh, Sh.; Acu, Mugur
Abstract : The motivation of the present paper is to define a new subclass of univalent functions associated with the q -analogue of the exponential function and the well-known Bell numbers based on subordination structure. Furthermore, we estimate the coefficient bound and extreme points. Also, geometric properties such as convexity and convolution preserving concept are investigated.